El riesgo de responsabilidad del órgano de administración de las cooperativas en situaciones de insolvencia, y de pérdidas patrimoniales - Sacristán Bergia, Fernando (REVESCO. Revista de Estudios Cooperativos, 2006)
The current paper covers the aspect of the cooperative company´s directors legal responsability in situations of patrimonial losses and insolvency. The Study tries to present wich is the current Law, for what truns out to be necesary bear in mind the different treatment on the different cooperative autonomic laws. The study takes in consideration the jurisprudential treatment, wich allows us to value the practical transcendency of the interpretation which is the Court to the recentt reforms. The responsability in the Insolvency Law is an object of tratment differentiated in the last paragraph.